THE EFFECTIVENESS OF GARLIC SQUARE (ALLIUM SATIVUM L.) ON THE GROWTH OF THE MALASSIEZIA FURFUR CAUSES PITIRIASIS VERSICOLLOR (IN VITRO) - DINDA NOVITA; NITA ANDRIANI (LP2MTBM MAKARIOZ, 2023)
Pityriasis versicolor is an infectious disease of the skin caused by the fungus Malassezia furfur species. According to WHO, the incidence of pityriasis versicolor in developing countries is 16% at the age of 13 years, 8-18% at the age of 14-15 years and 1% at the age of 5-9 years. To determine the effectiveness of garlic (Allium sativum L.) juice on the growth of the fungus Malassezia furfur that causes pityriasis versicolor. The research method used is experimental in vitro test with post test only control group design using disc diffusion method to see the role of garlic juice in inhibiting the growth of Malassezia furfur fungus. In this study the results obtained concentration of 10% with 15%, concentration of 10% with 20%, concentration of 20% with 5%, concentration of 15% with 20%, and concentration of 20% with positive control with p<0.05. The results of this study showed that garlic (Allium sativum L.) was not effective in inhibiting the growth of the fungus Malassezia furfur.